2023
DOI: 10.3389/fimmu.2023.891947
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and coronary artery disease risk in patients with diabetes: A Mendelian randomization study

Abstract: BackgroundPrevious observational studies have shown an association between smoking and coronary artery disease (CAD) in patients with diabetes. Whether this association reflects causality remains unestablished. This study aimed to explore the causal effect of smoking on CAD in patients with diabetes.MethodsGenetic signatures for smoking were extracted from a large genome-wide association study (GWAS), consisted of up to 1.2 million participants. Four smoking phenotypes were included: smoking initiation, cigare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Meanwhile, the increased levels of inflammatory factors further contribute to impaired glucose uptake and metabolism in blood vessels, forming a cycle of disordered glucose metabolism. ( van Helden et al, 2020 , Songzan et al, 2023 , O'Sullivan Jack et al, 2023 , Abdu Fuad et al, 2023 , Pasquale et al, 2021 , Choo et al, 2019 , Nordenskjöld et al, 2018 , Luying et al, 2023 , Marlene et al, 2022 , Hiroaki, 2014 , Bye Bailey et al, 2023 , Paula et al, 2023 , Driskill Jordan and Duojia, 2023 , Tedy et al, 2022 , Fangdi et al, 2022 , Elias et al, 2023 , Roshanzamir and Showkathali, 2013 ) Lipid metabolism disorder Lack of research temporarily. The role of cholesterol in the pathogenesis of MINOCA is controversial; total cholesterol is a predictor of pathogenesis in patients with NSTE MINOCA; a high LDL-C level is an independent risk factor for MACE in STE MINOCA; reducing Lp[a] levels improves survival in patients with MINOCA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the increased levels of inflammatory factors further contribute to impaired glucose uptake and metabolism in blood vessels, forming a cycle of disordered glucose metabolism. ( van Helden et al, 2020 , Songzan et al, 2023 , O'Sullivan Jack et al, 2023 , Abdu Fuad et al, 2023 , Pasquale et al, 2021 , Choo et al, 2019 , Nordenskjöld et al, 2018 , Luying et al, 2023 , Marlene et al, 2022 , Hiroaki, 2014 , Bye Bailey et al, 2023 , Paula et al, 2023 , Driskill Jordan and Duojia, 2023 , Tedy et al, 2022 , Fangdi et al, 2022 , Elias et al, 2023 , Roshanzamir and Showkathali, 2013 ) Lipid metabolism disorder Lack of research temporarily. The role of cholesterol in the pathogenesis of MINOCA is controversial; total cholesterol is a predictor of pathogenesis in patients with NSTE MINOCA; a high LDL-C level is an independent risk factor for MACE in STE MINOCA; reducing Lp[a] levels improves survival in patients with MINOCA.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically important glucose metabolism disorders mainly result in too high or low blood glucose concentrations ( van Helden et al, 2020 ). Previous studies have confirmed the association between diabetes and CAD prognosis ( Songzan et al, 2023 , O'Sullivan Jack et al, 2023 ), but the effect of diabetes on cardiovascular outcomes in patients with MINOCA is unclear.…”
Section: Effect Of Cardiometabolic Risk Factors On the Prognosis -+Of...mentioning
confidence: 96%
See 1 more Smart Citation
“…If not, the IVW model with fixed effects was used ( Shi et al., 2023 ). Meanwhile, we used MR-PRESSO and MR-Egger intercept tests to detect horizontal pleiotropy ( Chen et al., 2023 ). Finally, the leave-one-out sensitivity analysis was performed to examine if one single SNP drove the causal association.…”
Section: Methodsmentioning
confidence: 99%
“…Family history is also associated with the risk of mortality of CAD. [3] The renin-angiotensin-aldosterone system (RAAS) is a key modulator of cardiovascular and renal function. Clinical trials have demonstrated that inhibiting this system would reduce the risk of coronary events.…”
Section: Introductionmentioning
confidence: 99%